A Road to Trust - Labonne, Julien; Chase, Robert S. (2012)
We explore the relationship between transaction costs and generalized trust. Using panel data from 2100 households in 135 poor rural communities of the Philippines, we show that where costs of interactions are reduced there is an increase in generalized trust. These results have implications for the literature on the links between trust and growth. Indeed, rather than being an input to economic growth, trust might be a product of reduced costs of interactions which also favors growth. Specifically, we find that the individuals most likely to engage in exchange exhibit an increase in trust after road construction.